2018
DOI: 10.1137/17m1124498
|View full text |Cite
|
Sign up to set email alerts
|

On Blow-Up Solutions of Differential Equations with Poincaré-Type Compactifications

Abstract: We provide explicit criteria for blow-up solutions of autonomous ordinary differential equations. Ideas are based on the quasi-homogeneous desingularization (blowing-up) of singularities and compactifications of phase spaces, which suitably desingularize singularities at infinity. We derive several type of compactifications and show that dynamics at infinity is qualitatively independent of the choice of such compactifications. We also show that hyperbolic invariant sets, such as equilibria and periodic orbits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(108 citation statements)
references
References 14 publications
0
108
0
Order By: Relevance
“…Also, the inequality x i ≤ 1 is required for i = 1, · · · , N − 1 for the boundedness of exponential terms h 1,1−x m i ;m (s). In the same argument as [4], we can prove that divergent solutions of (1.1) correspond to global trajectories of (2.4) in {s > 0} asymptotic to equilibria (or general invariant sets) on the horizon {s = 0}. If, moreover, we can prove that maximal existence times t max of calculated solutions shown below are finite, then the corresponding divergent solutions are actually blow-up solutions.…”
Section: We Havementioning
confidence: 80%
See 3 more Smart Citations
“…Also, the inequality x i ≤ 1 is required for i = 1, · · · , N − 1 for the boundedness of exponential terms h 1,1−x m i ;m (s). In the same argument as [4], we can prove that divergent solutions of (1.1) correspond to global trajectories of (2.4) in {s > 0} asymptotic to equilibria (or general invariant sets) on the horizon {s = 0}. If, moreover, we can prove that maximal existence times t max of calculated solutions shown below are finite, then the corresponding divergent solutions are actually blow-up solutions.…”
Section: We Havementioning
confidence: 80%
“…Typically, compactifications are chosen so that the asymptotically dominant terms at infinity are selected appropriately. Such operations can be done for asymptotically polynomial vector fields and a geometric treatment of blow-up solutions is derived (e.g., [4]). However, the present vector field (1.1) contains exponential nonlinearity, and the general treatment of asymptotic behavior of vector fields at infinity is nontrivial.…”
Section: Desingularized Vector Field At Infinitymentioning
confidence: 99%
See 2 more Smart Citations
“…The rest of the paper is organized as follows. In Section 2, we review the approach and result shown in [14,16] about characterization of blow-up solutions in terms of trajectories on stable manifolds of invariant sets at infinity for appropriately associated vector fields. These results gives characterization of type-I blow-ups.…”
mentioning
confidence: 99%